THE MEANING OF TWO VALID MEANS OF EVIDENCE IN DETERMINING A SUSPECTS IN THE PRE-TRIAL PROCESS - Sultan Agung; Yuliati; Faizin Sulistio (CV. RADJA PUBLIKA, 2025)
The purpose of this study is to find out whether 2 (two) valid evidence is only based on the quality of the evidence or should the quality of the evidence; and analyze the difference between examining the quality of evidence and examining the subject matter at trial. The method of this research is normative juridical with conceptual, statutory and comparative approaches. The results of the study show that the proof of 2 valid evidence to establish a person as a suspect in the pretrial process does not focus on determining the material truth, but rather on procedural and formalistic aspects. Basing the decision on two pieces of evidence quantitatively can cause big problems for the judge so that in addition to having to pay attention to the amount of evidence, but also having to check the quality of the evidence as the principle of evidence in Perma Number 4 of 2016 emphasizes that the testing of the quality of this evidence must be carried out carefully and carefully, so that the legal process remains fair and does not harm the rights of the suspect.